Damage resistance, R-curve behavior and toughening mechanisms of ZrB2-based composites with SiC whiskers and ZrO2 fibers. Issue 2 (March 2015) - Lin, Jia; Huang, Yu; Zhang, Houan
Abstract: The damage tolerance and R -curve behavior of ZrB2 -based composites with SiC whiskers and ZrO2 fibers were investigated by using the envelope method. Obvious R -curve behavior was further observed in these composites, as a result of the combined effect of whisker toughening and transformation toughening. The SiC whiskers with high aspect ratio exhausted more fracture energy by deflection, bridging and pull-out during failure, and promoted the transformation toughening of ZrO2 fibers. It was found that these interactions produced a notable increase in toughness to 8.2 MPa m 1/2 . The relatively contribution of each toughening mechanism was estimated. This calculated value was in good agreement with the experimental results (8.0±0.5 MPa m 1/2 ) and the predictions of R -curve behavior (8.026 MPa m 1/2 ).